Automated System for Pouring and Filtration Tasks in Laboratory Applications. Issue 4 (19th May 2021) - Neubert, Sebastian; Junginger, Steffen; Roddelkopf, Thomas; Burgdorf, Simon‐Johannes; Stoll, Norbert; Thurow, Kerstin
Abstract: Using established needle‐ and tip‐based liquid‐handlers partially restricts applications that require the handling of greater sample amounts, options for filtration or handling of liquids with uncommon behavior. In this paper the prototype development of a versatile liquid pouring device (vLiPD) is described, which offers complementary features to usual liquid‐handling solutions. For mapping the container characteristics, a geometrical and an on 3D‐CAD‐model‐based approach are introduced and compared. Influences by the liquids' behaviors are compensated by liquid‐specific calibration factors. Abstract : Pouring tasks are essential in laboratory practice but still it cannot be found in laboratory automation even though it offers versatile advantages especially regarding the realization of end‐to‐end automation. In this paper the development and validation of an automated and integrable approach for a pouring device is presented.